ANALISIS POTENSI REFUSE DERIVED FUEL (RDF) DARI SAMPAH PADA TEMPAT PEMBUANGAN AKHIR (TPA) DI KABUPATEN TEGAL SEBAGAI BAHAN BAKAR INCINERATOR PIROLISIS - Mutiara Fadila Rania; I Gede Eka Lesmana; Eka Maulana (University of Muhammadiyah Jakarta, 2019)
The garbage dumping in Tegal Regency has reached 989.8 m3/day and increasing every year. The percentage of waste in Murareja landfill is dominated by plastic waste which is 40.15%. The plastic waste will be processed by pyrolysis by utilizing Refuse Derived Fuel (RDF) as its fuel. The percentage of garbage in Murareja TPA that can be used as RDF is quite high, which is 28.7%, consisting of 15.35% paper waste, 2.35% rubber / leather waste, 2% garbage cloth, 1% wood waste, and 8% plastic waste. The waste is considered potentially to be produced into RDF. The production of RDF aims to convert the combustible waste fraction from 4K1P waste (Paper, Wood, Fabrics, Rubber / Leather and Plastics) to be fueled. Therefore it is important to know how much potential of 4K1P waste to be processed into RDF, and how optimal calorific value of RDF is to be used as fuel of pyrolysis incinerator on Waste Power Generation at Murareja TPA, Tegal regency. Based on the result of the research that has been done, the theoretical value of the theoretical value of 4K1P RDF briquette is 3677.0945 - 5507.114 [kcal / kg]. From the actual data obtained with laboratory testing the value of RDF beverage caloric waste 4K1P RDF amounted to 3973.45 [kCal / kg]. The optimal calorific value of RDF required as a pyrolysis incinerator fuel is 3248.809 [kcal / kg]. Based on the results of laboratory tests, the percentage of moisture content, ash content, volatile content and carbon content are 4.68%, 11.64%, 7.81% and 75.87% respectively.